2015
DOI: 10.1589/jpts.27.3829
|View full text |Cite
|
Sign up to set email alerts
|

An effective model for observational learning to improve novel motor performance

Abstract: [Purpose] To investigate whether for observational learning involving a ball rotation task, an unskilled model showing clumsy finger movements is more effective than a skilled model‏. [Subjects and Methods] Thirty-six young adults were randomly assigned to one of three groups. The unskilled model observation group observed a video of a ball rotation task practiced by a person for a short time. The skilled model observation group observed another video of the same task practiced by the person for a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In this study, visual stimuli that would modulate mirror neuron activity were examined. The results show that the EEG mu rhythm is suppressed by the observation of actions on objects the hands in both conditions, reflecting activation of the MNS and consistent with previous studies of the mu rhythm 13 , 21 , 24 , 31 ) . These results suggest that mu suppression involves a range of structures that modulate motor preparation activities and are sensitive to visual input 13 ) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, visual stimuli that would modulate mirror neuron activity were examined. The results show that the EEG mu rhythm is suppressed by the observation of actions on objects the hands in both conditions, reflecting activation of the MNS and consistent with previous studies of the mu rhythm 13 , 21 , 24 , 31 ) . These results suggest that mu suppression involves a range of structures that modulate motor preparation activities and are sensitive to visual input 13 ) .…”
Section: Discussionsupporting
confidence: 91%
“…In other studies comparing brain waves in stroke patients and healthy subjects during action observation 15 ) , both groups showed significant differences in relative alpha power, suggesting action observation may be used as a therapeutic method for cognitive intervention. In a clinical setting, based on these brain wave changes, Kawasaki et al 31 ) showed that observational learning increased motor performance involving a ball rotation task, and Kim et al 32 ) suggested that action observation can enhance the walking performance of patients with post-stroke hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a common mechanism between VMI and action observation therapy (AOT). Previous studies of AOT have reported that observing a model with higher motor skills than the observer has a greater influence on motor performance [ 44 ]. In addition, most previous studies have presented image video models with a higher motor performance than the observer and have reported activation of brain activity and improvement of physical function [ 20 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The motor task was a ball-rotation task in which two balls were rotated in the palm of the left hand (Kawasaki et al, 2015(Kawasaki et al, , 2019. The balls (Uchida-denshi, Hachioji, Japan) were made from resin and were 50 mm in diameter, weighed 60 g each, and had a smooth surface.…”
Section: Methodsmentioning
confidence: 99%